2007
DOI: 10.1016/j.virol.2007.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Arenavirus entry occurs through a cholesterol-dependent, non-caveolar, clathrin-mediated endocytic mechanism

Abstract: Arenaviruses are important causes of viral hemorrhagic fevers in humans. Arenavirus infection of cells occurs via a pH-dependent endocytic route, but detailed studies of entry pathways have not been done. We investigated the role of cell membrane cholesterol, caveolae, and clathrin coated pits in infection by Lassa virus (LASV), which utilizes alpha-dystroglycan (alpha-DG) as a receptor, and Pichindé virus (PICV), which does not. Depletion of cellular cholesterol by treatment with methyl betacyclodextrin (Mbet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 64 publications
3
46
2
Order By: Relevance
“…3c). Furthermore, as severe cholesterol depletion has been shown to also inhibit CME (Vela et al, 2007), we confirmed that MbCD treatment did not inhibit uptake of Alexa-568 transferrin (data not shown). These data suggest that MNV-1 infection is cholesterol-sensitive and likely to be mediated by a lipid-raft-dependent pathway.…”
Section: Depletion Of Cellular Cholesterol Inhibits Mnv-1 Endocytosissupporting
confidence: 79%
“…3c). Furthermore, as severe cholesterol depletion has been shown to also inhibit CME (Vela et al, 2007), we confirmed that MbCD treatment did not inhibit uptake of Alexa-568 transferrin (data not shown). These data suggest that MNV-1 infection is cholesterol-sensitive and likely to be mediated by a lipid-raft-dependent pathway.…”
Section: Depletion Of Cellular Cholesterol Inhibits Mnv-1 Endocytosissupporting
confidence: 79%
“…The involvement of lipids in clathrin-mediated pathways has been previously reported, especially for the uptake of toxins and viruses toward the cytoplasm (45,46). Also, internalization of the apolipoprotein E receptor 2 internalizes through a clathrin-mediated pathway after association with caveolar and noncaveolar lipid rafts (55).…”
Section: Discussionmentioning
confidence: 88%
“…Such a mechanism has been previously described for the entry of viruses and bacterial toxins in the cell (45,46).…”
Section: Micb Endocytosis and Clathrin-independent Pathwaysmentioning
confidence: 81%
“…First, depletion of cellular cholesterol by methyl-␤-cyclodextrin has been reported to inhibit arenavirus replication (61,69), and because the arenavirus receptors TfR1 and ␣-dystroglycan (15, 54, 64) do not themselves associate with lipid rafts, we surmised that the requirement for cholesterol might arise in virus egress. Second, myristoylation is essential for both GPC and the Z matrix protein (52,77), and the addition of a saturated fatty acid moiety in raft proteins is often required for association (39,46).…”
Section: Discussionmentioning
confidence: 99%